Executive functioning in preschoolers with specific language impairment - Vissers, Constance; Koolen, Sophieke; Hermans, Daan; Scheper, Annette; Knoors, Harry (Frontiers in Psychology, 2015)
The pathogenesis of Specific Language Impairment (SLI) is still largely beyond our understanding. In this review, a neuropsychological perspective on language impairments in SLI is taken, focusing specifically on executive functioning (EF) in preschoolers (age range: 2.6-6.1 years) with SLI. Based on the studies described in this review, it can be concluded that similar to school-aged children with SLI, preschoolers with SLI show difficulties in working memory, inhibition and shifting, as revealed by both performance based measures and behavioural ratings. It seems plausible that a complex, reciprocal relationship exists between language and EF throughout development. Future research is needed to examine if, and if yes how, language and EF interact in SLI. Broad neuropsychological assessment in which both language and EF are taken into account may contribute to early detection of SLI. This in turn can lead to early and tailored treatment of children with (suspected) SLI aimed not only at stimulating language development but also at strengthening EF.